Dietary vitamin E dosage and source affects meat quality parameters in light weight lambs. (9th October 2017) - Leal, Leonel N; Beltrán, José A; Alonso, Verónica; Bello, José M; den Hartog, Leo A; Hendriks, Wouter H; Martín‐Tereso, Javier
Abstract: BACKGROUND: Supra‐nutritional vitamin E supplementation is a commonly used approach to delay lipid oxidation and colour deterioration in lamb and beef meat marketed under modified atmosphere packaging. However, these applications lack a precise calibration of dose for the desired effect and, in addition, limited information is available regarding the use of natural vitamin E for this purpose. RESULTS: Three hundred and sixty Rasa Aragonesa lambs were fed diets supplemented with all‐rac ‐ α ‐tocopheryl acetate (250, 500, 1000 and 2000 mg kg –1 compound feed), RRR‐ α ‐tocopheryl acetate (125, 250, 500 and 1000 mg kg –1 compound feed) and a basal diet without vitamin E supplementation for 14 days before slaughter at 25.8 ± 1.67 kg body weight. Vitamin E supplementation had no effect ( P  > 0.05) on average daily weight gain, feed intake and feed efficiency. Display time had larger effects on lipid oxidation, colour stability, myoglobin forms and meat discolouration parameters compared to vitamin E supplementation. However, vitamin E source and dosage significantly extended meat shelf‐life as indicated by lipid oxidation, redness, hue angle, metmyoglobin formation, deoxymyoglobin formation, A 580–630 and I SO2 . CONCLUSION: The quantification of these effects demonstrated that the biological activity value of 1.36 used to distinguish both vitamin E sources is not appropriate for meat quality enhancing properties. © 2017 Society of Chemical Industry